SOCIAL WORK AND SOCIAL MOVEMENTS: REFLECTIONS ABOUT THE HUMAN EMANCIPATION PROCESS - Benevides Dias Lima, Ester; Figueiredo do Amaral Cruz, Júlia; Faria Pinheiro, Luci; do Livramento, Victória (Revista Serviço Social em Perspectiva, 2022)
Abstract: It is a thematic work that, through the review of the bibliography and videography of the undergraduate course "Social Movements and Social Issue", we propose to stimulate the production on the object of study, in an articulated way to the ethical-political principles and values of Social Work in its training policy, affirming the importance of deepening the professional role in the formation of class consciousness, in the context of radicalization of the order of capital. In this sense, based on Marxist theory, the article addresses the relationship between social issues and social movements, highlighting social struggles as the means by which the working class reacts against the production and expanded reproduction of social inequalities inherent to capitalism, as well as, the process of awareness “in itself” and “for itself” of the working class. Starting from this discussion, we understand that the categories totality and daily life are fundamental for the analysis of the method that must understand the political organization of the working class. In addition, we defend the effective articulation between Social Work and social movements as an integral part of their professional training. Finally, we examine the resurgence of the neoliberal agenda in Brazil and point out ways for the working class to resist the established barbarism.